Leasing and remanufacturing strategies with pricing and inventory control - Demirok, Nurcan. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2011., 2011)
We consider infinite horizon inventory policies for a company which satisfies customer demand by either selling or leasing a product. If the product is leased, it can be leased for a different number of periods. The customer demand follows a Poisson process whose mean is a function of the price. The company has manufacturing, refurbishing and remanufacturing options for building-up inventory. The new products and the products returned by the customers that are subject to remanufacturing or refurbishing process are collected into the same finished goods inventory. It is assumed that significantly worn-out ones among the returned products are disposed of from the system. In the model, we consider an (S - 1, S) type policy for controlling the inventory and determine the optimal inventory level as well as the optimal leasing and selling price of the product. Our analytical model assumes that a used product can return to the system infinitely many times. We use the optimal price and inventory levels obtained from the analytical model in a simulation model which considers the more realistic case of a finite number of returns. We calculate the average profit per unit time including revenue from leasing and sales, inventory holding costs in the system, backorder and lost sales costs. We discuss the results of the analytical model and compare them with the simulation model results, and provide insights for the decision makers.
Keywords: Inventory control -- Mathematical models.; Spare parts -- Inventory control.; Supply and demand.